Principles of physical optics - Bennett, Charles A. (Hoboken, NJ : Wiley, 2022)
"The new edition of this accessible optics textbook is designed to support a one-semester first course in optics, building a firm foundation in physical optics, along with practical experience in a range of mathematical applications such as matrix methods, Fourier analysis, and complex algebra. It has been completely revised to aid teaching and self-study by a re-arrangement of topics and inclusion of 20% more worked examples and 50% more homework problems. The prerequisites assumed in this text are limited to the standard introductory sequences in calculus and calculus-based physics. Principles of electricity and magnetism are developed as needed, beginning with integral forms of Maxwell's equations. A derivation of the electromagnetic wave equations is included, as is a thorough determination of all properties of transverse electromagnetic waves. The material is organized to allow coverage at least through Chapter 8 on lasers within a three hour, one-semester course. Further and more advanced topics have been included as starred sections or moved to appendices. Chapter 9 (Optical Imaging) and Chapter 10 (Nonlinear Optics and Dispersion) are available for courses that maintain a more lively pace, or perhaps do not include a complete coverage of earlier chapters"--
Includes bibliographical references and index.
Keywords: Optics